AGS3-based optogenetic GDI induces GPCR-independent Gβγ signalling and macrophage migration - Waruna Thotamune; Sithurandi Ubeysinghe; Chathuri Rajarathna; Dinesh Kankanamge; Koshala Olupothage; Aditya Chandu; Bryan A. Copits; Ajith Karunarathne (Open Biology)
G-protein-coupled receptors (GPCRs) are efficient guanine nucleotide exchange factors (GEFs) and exchange GDP to GTP on the Gα subunit of G-protein heterotrimers in response to various extracellular stimuli, including neurotransmitters and light. GPCRs primarily broadcast signals through activated G proteins, GαGTP and free Gβγ and are major disease drivers. Evidence shows that the ambient low threshold signalling required for cells is likely supplemented by signalling regulators such as non-GPCR GEFs and guanine nucleotide dissociation inhibitors (GDIs). Activators of G-protein signalling 3 (AGS3) are recognized as a GDI involved in multiple health and disease-related processes. Nevertheless, understanding of AGS3 is limited, and no significant information is available on its structure–function relationship or signalling regulation in living cells. Here, we employed in silico structure-guided engineering of a novel optogenetic GDI, based on the AGS3’s G-protein regulatory motif, to understand its GDI activity and induce standalone Gβγ signalling in living cells on optical command. Our results demonstrate that plasma membrane recruitment of OptoGDI efficiently releases Gβγ, and its subcellular targeting generated localized PIP3 and triggered macrophage migration. Therefore, we propose OptoGDI as a powerful tool for optically dissecting GDI-mediated signalling pathways and triggering GPCR-independent Gβγ signalling in cells and in vivo.